Geotourism Development Strategy in An Effort to Increase the Community's Economy in Nagari Aie Angek, X Koto District, Tanah Datar Regency, West Sumatra (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Study This done with objective For know and analyze the development strategy geotourism in increase economy the people of Nagari Aie Angek Kec X Koto Kab . Flat Land. Type study This is Qualitative descriptive , purposeful For know mark variable free without connect or make comparison with other variables. Data used in study This is qualitative data form answer through interview , Observation , Study Literature and Documentation . Method data analysis was performed with use technique SWOT analysis . Research results This show that Still development strategy is needed Geotourism in the nagari whiny with magnitude potential , strengths and opportunities to grow and develop _ _ as well as can more increase economy public local